Analysis of Physical Fitness of Volleyball Extracurricular Students at SMAN 3 Bengkulu Selatan - Zopan Sopyan; Rivaldo Fernando; M. Rahman Hapis J; Eggy Fikri Pratama; David Cahyono Putra; Dolly Apriansyah (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the physical fitness level of students participating in volleyball extracurricular activities at SMAN 3 Bengkulu Selatan. Physical fitness is a crucial factor in supporting students' athletic performance and health. This study employed a descriptive quantitative method with a survey approach. The subjects of the study were 30 students who are active members of the volleyball extracurricular team. The instrument used was the Indonesian Physical Fitness Test (TKJI) for the 16–19 age group, which covers five main physical components. The results showed that the students' physical fitness level is generally in the